Neonatal mortality rate in Iran: the Iranian Perinatal Mortality Surveillance System - Mohammad Ali Heidarnia; Alireza Abadi; Mohammad Esmaeil Motlagh; Mohammad Heidarzadeh; Abbas Habibelahi; Hosein Dalili; Farima Raji (Hygeia Press di Corridori Marinella, 2018)
Background: Neonatal mortality is the major proportion of children mortality under five years and it is considered as the main health indicator in the first year of life. This paper has aimed to review the neonatal mortality in the numbers recorded at the Iranian Perinatal Mortality Surveillance System (IPMSS) by Iran Ministry of Health and Medical Education. Methods: A descriptive study was done in 2014. For assessment of sampling quality and quantity, 24 hospitals randomly were selected. Recorded information, related to perinatal mortality (deaths from 22 completed weeks of gestation until 30 completed days after birth inclusive of stillbirths and neonatal mortality) from selected hospitals, was compared with recorded data in IPMSS. Results: Results showed that, out of 1,725 perinatal deaths occurred in hospitals, 1,480 (85.80%) deaths were recorded in IPMSS. Of 1,041 neonatal deaths that occurred in hospitals (in hospital wards and delivery rooms), 875 (84.05%) were in IPMSS. It shows that a correction coefficient for hospital neonatal mortality was 1.1904. Based on analyzing process, correction coefficients for stillbirth reported by hospitals, stillbirth for all over the country and perinatal death were 1.130, 1.1775 and 1.2443, respectively. Considering these correction coefficients - that enabled to calculate 15,130 neonatal deaths - and 1,421,689 live births (according to Statistics Center) in 2012, neonatal mortality rate was 10.64 in 1,000 live births. Conclusion: Our data showed some problems in the registration system. Although implementation and supervision of such Surveillance System are not easy, they are essential and provide valuable data in perinatal audit and neonatal health care practices.